2019
DOI: 10.1002/iub.2069
|View full text |Cite
|
Sign up to set email alerts
|

p53‐induced long non‐coding RNA PGM5‐AS1 inhibits the progression of esophageal squamous cell carcinoma through regulating miR‐466/PTEN axis

Abstract: A growing body of evidence suggests that long non‐coding RNA (lncRNA) is aberrantly expressed in human cancer and linked to cancer initiation and development. We previously identified Homo sapiens PGM5 antisense RNA 1 (PGM5‐AS1) as a novel esophageal squamous cell carcinoma (ESCC)‐related lncRNA by performing high‐throughput RNA sequencing. However, its clinical implication and biological function in ESCC are still uncharacterized. In the present study, we found that PGM5‐AS1 was frequently downregulated in ES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…HCC is one of the malignant diseases which has threatened the health of human, and miRNA dysfunction has been found as a key cause of cancer formation [ 15 ]. MiR-466 locates on chromosome 3, and several studies have indicated that miR-466 is significantly downregulated in some tumor cells and involves the regulations of the proliferation and invasion of the tumors [ 16 ]. In this study, the expression levels of miR-466 in HCC tissues and cell lines were investigated, and the effects of miR-466 on the phenotype of HCC cells such as proliferation, invasion, and apoptosis were also explored.…”
Section: Discussionmentioning
confidence: 99%
“…HCC is one of the malignant diseases which has threatened the health of human, and miRNA dysfunction has been found as a key cause of cancer formation [ 15 ]. MiR-466 locates on chromosome 3, and several studies have indicated that miR-466 is significantly downregulated in some tumor cells and involves the regulations of the proliferation and invasion of the tumors [ 16 ]. In this study, the expression levels of miR-466 in HCC tissues and cell lines were investigated, and the effects of miR-466 on the phenotype of HCC cells such as proliferation, invasion, and apoptosis were also explored.…”
Section: Discussionmentioning
confidence: 99%
“…The lncRNA PGM5-AS1 has been limitedly studied (n=4 in PubMed under 'PGM5-AS1'). Evidence suggests PGM5-AS1 suppresses esophageal squamous cell carcinoma by facilitating PTEN actions though sponging miR-466 (224). Apart from SNHG1, CRNDE, PART1 and PGM5-AS1, the others in the 7-lncRNA panel (Table VI) have not yet been reported, at least to the best of our knowledge…”
Section: Gene Expression-based Biomarkersmentioning
confidence: 99%
“…Esophageal squamous cell carcinoma (ESCC), which accounts for 90% of esophageal cancer, is the sixth leading cause of cancer-associated mortality, especially in several developing countries (1). Despite developments in medical and surgical treatment, the 5-year survival rate of ESCC is only 15-25%, largely because of recurrence of primary treatment and late stage diagnosis (2,3).…”
Section: Introductionmentioning
confidence: 99%